ROLE OF ECG IN DIAGNOSIS OF INHERITED ARRHYTHMIA SYNDROMES - Jurčević, Ružica; Angelkov, Lazar; Vukajlović, Dejan; Ristić, Velibor; Kojić, Dejan; Tomović, Milosav; Grbović, Aleksandra; Babić, Miloš; Tasić, Nebojša; Bojić, Milovan (Medicinski podmladak, 2020)
The aim of this paper is to define role of ECG in diagnosis, prognosis and treatment of inherited arrhythmias syndromes. Brugada Syndrome diagnosis is established in presence of coved type ST-segment elevation (type 1) ≥ 2mm in ≥ 1 of the right precordial leads V1 to V2. Long QT Syndrome is diagnosed when one of factors is present: QTc ≥ 480 ms, QTc ≥ 460 ms in patients with unexplained syncope, pathogenic mutation or risk skore > 3. Polimorfic ventricular tachycardia (VT) Torsades de Pointes have specific presentation in ECG with characteristic illusion of a twisting of the QRS complex around the isoelectric baseline. ECG early repolarization pattern in patiets resuscitated from otherwise unexplained ventricular fibrillation (VF)/ polymorphic VT or in a sudden cardiac death (SCD) victims makes diagnosis of Early Repolarization Syndrome. Short QT Syndrome is diagnosed in the presence of a QTc ≤ 340ms or QTc ˂ 360ms with one or more of following factors: a pathogenic mutation, survival of a VT/VF episodes, family history of this disease and SCD in family at age ≤ 40. Catecholaminergic Polymorphic Ventricular Tachycardia has ECG appearance of bidirectional VT or polymorphic ventricular premature beats or VT induced by exercise or catecholamine.